The Effect of Information Technology, Work Discipline and Work Motivation On the Performance of State Civil Apparatus in Menui District, Morowali Regency - Arifin, Arifin; Adrianto, Adrianto; Razak, Abdul; Hajar, Ibnu (Riviera Publishing, 2022)
This study aims to determine how much influence information technology, work discipline and work motivation have on employee performance at the Menui Islands sub-district office. Inferential statistical analysis method with multiple linear regression model, census retrieval. This study used a questionnaire given to 23 employees of the District Office of Menui Islands. Furthermore, the data were analyzed using quantitative descriptive. The results showed that information technology, work discipline and work motivation simultaneously had a positive and significant effect on employee performance. Then partially each variable has a positive and significant effect on the performance of the employees of the Menui Islands sub-district. After the data is processed, the resulting value (r) of 0.972 indicates a strong positive relationship. The contribution of the influence of information technology, work discipline and work motivation on employee performance is 97.2% and the remaining 2.8%. influenced by variables not examined. Hypothesis testing is proven to have an effect on information technology, work discipline and work motivation on employee performance at the Menui Islands sub-district office.